how to put this in vertex form:

-2(2x-1)(x+4)

1 answer

y= -2(2x-1)(x+4)
-y/2 = (2x^2 +7x -4 )
-y/4 = x^2 +7/2 x -2
-y/4 + 2 = x^2 +7/2 x
-y/4 + 2 + 49/16 = x^2 + 7/2 x + 49/16
-y/4 + 81/16 = (x+7/4)^2
-1/4 (y-81/4) = (x+7/4)^2
(-7/4, 81/4)
Similar Questions
    1. answers icon 18 answers
  1. What are the vertex and focus of the parabola with equation y=x2+8x+10?Identify the vertex. (1 point) Responses vertex: (-4, 6)
    1. answers icon 1 answer
  2. write the vertex form equation of each parabola.1) Vertex:(-5,8), Focus:(-21/4, 8) 2) Vertex:(-6,-9), Directrix: x= 47/8
    1. answers icon 4 answers
  3. What are the vertex and focus of the parabola with equation y=x2−6x+15? Identify the vertex. (1 point) Responses vertex: (6,
    1. answers icon 1 answer
more similar questions